2001
DOI: 10.1053/jhep.2001.22499
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic uptake of organic anions affects the plasma bilirubin level in subjects with Gilbert's syndrome mutations in UGT1A1

Abstract: Although in Gilbert's syndrome (GS), bilirubin glucuronidation is impaired due to an extra TA in the TATA box of the promoter of the gene for bilirubin UDP-glucuronosyltransferase 1 (UGT1A1), many GS homozygotes lack unconjugated hyperbilirubinemia. Accordingly, an additional defect in bilirubin transport might be required for phenotypic expression. Plasma bilirubin and the early fractional hepatic uptake rate (BSP K 1 ) of a low dose of tetrabromosulfophthalein (0.59 mol/kg) were determined in (1) 15 unrelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In contrast, unconjugated hyperbilirubinemia is caused by the complete absence of UGT1A1 (Crigler-Najjar syndrome type 1) or decreased activity (10% activity in Crigler-Najjar type 2 and 30% activity in Gilbert syndrome) of this enzyme Bosma et al, 1995). In addition to deficient UGT-mediated glucuronidation, decreased uptake from the blood into the liver was also suggested to play a role in unconjugated hyperbilirubinemia (Martin et al, 1976;Persico et al, 2001), which has been shown for OATP1B1, where polymorphisms in this transporter's gene are associated with elevated serum bilirubin levels (Roth et al, 2012). Furthermore, drug-induced unconjugated hyperbilirubinemia by rifamycin SV, indinavir, and cyclosporin A was reported to be due to an inhibition of this OATP family member (Campbell et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, unconjugated hyperbilirubinemia is caused by the complete absence of UGT1A1 (Crigler-Najjar syndrome type 1) or decreased activity (10% activity in Crigler-Najjar type 2 and 30% activity in Gilbert syndrome) of this enzyme Bosma et al, 1995). In addition to deficient UGT-mediated glucuronidation, decreased uptake from the blood into the liver was also suggested to play a role in unconjugated hyperbilirubinemia (Martin et al, 1976;Persico et al, 2001), which has been shown for OATP1B1, where polymorphisms in this transporter's gene are associated with elevated serum bilirubin levels (Roth et al, 2012). Furthermore, drug-induced unconjugated hyperbilirubinemia by rifamycin SV, indinavir, and cyclosporin A was reported to be due to an inhibition of this OATP family member (Campbell et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…After UDP-glucuronosyltransferase (UGT) 1A1-mediated glucuronidation, bilirubin monoglucuronides and diglucuronides are exported from hepatocytes into bile via the ATP-binding cassette (ABC) transporter multidrug resistanceassociated protein (MRP) 2 (Kamisako et al, 1999). Patients with mild unconjugated hyperbilirubinemia resulting from Gilbert syndrome show deficient UGT activity but also a decreased bilirubin uptake into the liver (Martin et al, 1976;Persico et al, 2001). Therefore, a contribution of hepatocellular bilirubin uptake by transport processes to unconjugated hyperbilirubinemia has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Although, homozygous mutations in the promoter of bilirubin UDP-glucuronosyltransferase appear to be necessary for the syndrome to manifest itself (20), a genetically determined polymorphism(s) in a bilirubin uptake carrier is also thought to contribute to the pathogenesis of this disorder (21,22). Such a role for OATP-C is plausible because no other human OATPs have yet been shown to be capable of transporting unconjugated bilirubin (22). However, a role for OATP-C mutations as a component of Gilbert's syndrome awaits confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes for UDPGlucronyltransferase and thus the defective conjugating enzyme leads to the hepatic jaundice. [22][23][24] Any defect in the hepatic excretory mechanism of bilirubin can also cause hepatic jaundice. The excretory mechanisms involve hepatocytic bile acid-independent secretion, hepatocytic bile acid-dependent secretion and bile ductular secretion.…”
Section: Hepatic Jaundicementioning
confidence: 99%